2019
DOI: 10.1029/2018gl080554
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime fCO2 Variability in the Subpolar North Atlantic Since 2004

Abstract: Winter data of surface ocean temperature (SST), salinity (SSS) and CO2 fugacity (fCO2) collected on the VOS M/V Nuka Arctica in the subpolar North Atlantic between 2004 and 2017 are used to establish trends, drivers, and interannual variability. Over the period, waters cooled and freshened, and the fCO2 increased at a rate similar to the atmospheric CO2 growth rate. When accounting for the freshening, the inferred increase in dissolved inorganic carbon (DIC) was found to be approximately twice that expected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 66 publications
(163 reference statements)
4
36
0
Order By: Relevance
“…These independent estimates confirm that in the NASPG the observed long-term DIC trend and derived trends for f CO 2 and pH in surface waters (Table 2, are mostly linked with anthropogenic CO 2 uptake. The same conclusion was drawn for the subpolar mode waters found in subsurface layers in the NASPG (Vázquez-Rodríguez et al, 2012;García-Ibáñez et al, 2016;Fröb et al, 2018). For example, based on data collected in 1981, Vázquez-Rodríguez et al (2012 estimated that 75 % of the observed pH decrease (−0.0019 yr −1 ) in the subarctic intermediate waters (SAIW) in the Irminger Basin is due to anthropogenic DIC.…”
Section: Long-term Trend and Anthropogenic Comentioning
confidence: 53%
See 1 more Smart Citation
“…These independent estimates confirm that in the NASPG the observed long-term DIC trend and derived trends for f CO 2 and pH in surface waters (Table 2, are mostly linked with anthropogenic CO 2 uptake. The same conclusion was drawn for the subpolar mode waters found in subsurface layers in the NASPG (Vázquez-Rodríguez et al, 2012;García-Ibáñez et al, 2016;Fröb et al, 2018). For example, based on data collected in 1981, Vázquez-Rodríguez et al (2012 estimated that 75 % of the observed pH decrease (−0.0019 yr −1 ) in the subarctic intermediate waters (SAIW) in the Irminger Basin is due to anthropogenic DIC.…”
Section: Long-term Trend and Anthropogenic Comentioning
confidence: 53%
“…For example, based on data collected in 1981, Vázquez-Rodríguez et al (2012 estimated that 75 % of the observed pH decrease (−0.0019 yr −1 ) in the subarctic intermediate waters (SAIW) in the Irminger Basin is due to anthropogenic DIC. García-Ibáñez et al (2016), incorporating four additional cruises (2010-2015), estimated a pH decrease of around −0.0018 yr −1 over 1991-2015 in the subpolar mode waters (SPMW) found at around 200-300 m in the Irminger Basin. They also conclude that in the SPMW the pH decrease is dominated by DIC increase (+0.82 µmol kg −1 yr −1 ) through anthropogenic CO 2 (C-ant trend of +0.9 µmol kg −1 yr −1 ) but this is modulated by a pH increase over time due to an increase in alkalinity (about +0.11 µmol kg −1 yr −1 ).…”
Section: Long-term Trend and Anthropogenic Comentioning
confidence: 99%
“…The 2005 and 2008 cruise data have been released as part of the GLODAPv2 data synthesis . Similar water column carbonate measurements were also carried out in April 2015 on R/V GO Sars (Fröb et al, 2019). The 2015 cruise covered an east-west section perpendicular to the Norwegian west coast (59.3°N, 3-4°E; Figure 1, blue filled circles) and the data are available at https://cchdo.ucsd.edu/cruise/58GS20150410.…”
Section: Cruise Datamentioning
confidence: 81%
“…Estimates based on summer-only data typically show large interannual variations (Thomas et al, 2007;Salt et al, 2013), which led to the conclusion that here the interannual variability masks the actual long term trend. The approach to use winter-only data (Fröb et al, 2019;Omar et al, 2019), on the other hand, is based on the assumption that during this season the influence of biological processes is negligible and therefore winter data can be used to establish a baseline trend. However, also using winter-only data has its drawbacks.…”
mentioning
confidence: 99%